Tree Species Composition and Diversity in Subtropical Forest of Manipur, North-East India - meetei, Shougrakpam Bijen; Das, Ashesh Kumar; Singh, E. J. (Indian Forester, 2017)
Forest conservation and management require proper understanding of the structure and composition of particular forests in relation to other forests, and its surrounding land uses. The present study deals on the tree species diversity and status of indigenous tree species in the two subtropical mixed broad leaved forests of Senapati district, Manipur, North-east India. Vegetation analysis of two forest sites showed high tree densities (2631-3079 ind. ha-1). Fagaceae was found to be dominant family at both sites. The Shannon diversity index in both the sites was in the range of 2.44-2.80 and Simpson index was recorded to be 0.10-0.13. The quantitative similarity index 0.33 showed that the two forest sites have less species in common. The reverse J-shaped density distribution structure curve showed that tree diversity decreased with increase in girth classes. In total, the two forest sites showed a good stage of growing period with high species composition.